Vključujoči univerzitetni kampusi - Campos, Pablo (Urbani izziv, 2021)
The international university context is generating multiple dynamics of innovation. A relevant issue is the creation of inclusive campuses. This text studies keys to spatial planning on the urban and architectural scales and offers functional recommendations to create campuses that promote wellbeing and cognitive accessibility for people with intellectual disabilities. The goal is to inspire inclusive environments, promote an appropriation of the space, and reinforce a sense of belonging, emphasizing aspects such as the psychological and emotional perception of university environments. Based on this exploration, the text discusses a set of planning guidelines and architectural typologies with an inclusive scope. It begins by studying paradigms taken from the historical university legacy: the cloister and the campus. After this, the article focuses on aspects that inspire the integral planning of campuses to reinforce social inclusion: communities of learning, typologies of spatial composition, the human scale, edges, nature, the aesthetic component, and functional strategies. The text finishes by presenting a range of conclusions on how to supply those criteria and types so that campuses can be planned with higher quality with the goal of transforming them into inclusive environments, providing guidelines that can optimize them for all kinds of users.
Keywords: arhitektura; intelektualna oviranost; intellectual disabilities; social inclusion; socialna vključenost; university campus; univerzitetni kampusi; urban planning; urbanistično načrtovanje